2013
DOI: 10.1108/17471111311307787
|View full text |Cite
|
Sign up to set email alerts
|

Environmental attitude and ecological behaviour of Indian consumers

Abstract: Purpose -To create a sustainable environment, the aim of this study is to explore and identify the components of environmental attitude that can drive the specific ecological behaviour of Indian consumers. Further, it defines environmental attitude components as moderators and investigates them as predictor of ecological behaviour.Design/methodology/approach -The constructs of environmental attitude (EA) and ecological behaviour (EB) are measured using standardized scales with modifications that represent demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 31 publications
1
49
0
1
Order By: Relevance
“…Thus, these implicit attitudes meet the right place in the TPB by Ajzen (). Moreover, the link between cross‐cultural elements and TPB helps to understand the difference between environmental attitudes among Indian consumers studied by Singh and Gupta () and Swiss consumers studied by Tanner and Kast ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these implicit attitudes meet the right place in the TPB by Ajzen (). Moreover, the link between cross‐cultural elements and TPB helps to understand the difference between environmental attitudes among Indian consumers studied by Singh and Gupta () and Swiss consumers studied by Tanner and Kast ().…”
Section: Resultsmentioning
confidence: 99%
“…() argued that, first, environmental knowledge and environmental values are significant preconditions of ecological behaviour intention. Second, ecological behaviour intention predicts ecological behaviour remarkably well, as found by Singh and Gupta () in a survey of Indian consumers. Third, the relationship between environmental attitude and ecological behaviour remains comparable even for ideologically heterogeneous groups.…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…These authors based their hypotheses on the theory of reasoned action (TRA), first developed by Ajzen and Fishbein (), which examines the attitude–behavior relationship. They supported the application of TRA to predict green product consumption and stated that a positive attitude and concern toward the environment increases the effort that individuals make to reduce their environmental impact (Singh & Gupta, ).…”
Section: Background Theory and Hypothesis Developmentmentioning
confidence: 98%
“…In the context of tourism, Wei et al (2013) observed a link between social engagement and environmental concerns among tourists. Singh and Gupta (2013) also point out that environmental concerns have an influence on behaviour in the context of consumption. Responsible tourism is not only concerned with the physical environment but also with social wellbeing, such as ensuring that tourism does not have a negative impact on the lives of local communities (Uriely et al, 2007).…”
Section: Involvement In Responsible Tourismmentioning
confidence: 97%